Synthesis, Structural Study and Biological Activity Evaluation of Cr (III), Mn (II), Zn (II), Cd (II) and Hg (II) Complexes with New Schiff Base Ligand Derived from Isatin - Wurood Ali Jaafar (Journal of Global Pharma Technology, 2018)
The New Schiff base [3E-3-((1,5-dimethyl-3-((4-nitrophenyl)imino)-2-phenyl-2,3-dihydro-1H-pyrazol-4-yl)imino)indolin-2-one][L] was prepared by two steps, 4-aminoantipyrine was reacted with isatin in the first step to produce the precursor [A], then [A] was reacted with p-nitroaniline to give a new tridentate ligand [L]. this ligand[L] was reacted with some metal ions in Cr (III), Mn(II), Zn(II), Cd(II) and Hg(II)to give a series of new metal compexes of the general molecular formula [M(L)2]Cln , where: M=Cr(III), n=3; M=Mn(II),Zn(II),Cd(II) and Hg(II), n=2. All compounds were have been characterized by spectroscopic methods [ IR, UV-Vis, atomic absorption],elemental microanalysis, chloride content, magnetic susceptibility, conductivity measurements along with 1H,13C-NMR and mass spectroscopy for ligand [L] only. According to the results of the above techniques, the suggested geometrical structures for all prepared complexes were octahedral formula.Keywords: Schiff base, Isatin, 4- amino antipyrine.